Impact of CrossFit intervention on mental health and well-being among first-year law students - Valentina Stefanica; Halil İbrahim Ceylan; Liviu Mihailescu; Dana Badau; Marko Joksimović; Daniel Rosu (Humanities & Social Sciences Communications)
Abstract This study investigates the impact of a four-week CrossFit intervention on the physical and mental well-being of 75 first-year law students, divided equally into three groups: outdoor CrossFit (n = 25), indoor CrossFit (n = 25), and a control group (n = 25). A linear mixed effects model (LMM) was employed to assess the intervention’s effects while accounting for intraindividual variability and repeated measures. Participants in both active groups demonstrated statistically significant improvements in physical health (p < 0.001, Cohen’s d > 1.20), as measured by the WHOQOL-BREF Physical Health domain. Psychological well-being (WHOQOL-BREF Domain 2) also improved significantly in both groups (p < 0.001), while the control group showed no such gains. Mental health indicators—including depression, anxiety, and stress—measured by the DASS-21, decreased significantly in both intervention groups (p < 0.001), with large to very large effect sizes (Cohen’s d ranging from 0.87 to 1.69). The control group exhibited no significant improvements. Although no significant differences were found between the indoor and outdoor groups in most domains, outdoor training showed a significantly greater effect on environmental health (WHOQOL-BREF Domain 4, p < 0.01, Cohen’s d = 1.39), underscoring the added benefit of exercising in natural settings. Social relationships (Domain 3) remained unaffected across all groups. These findings highlight CrossFit’s efficacy as a structured intervention for enhancing physical and psychological well-being in high-stress academic environments. Moreover, training outdoors appears to offer additional environmental benefits that may further enhance students’ perceived quality of life.